Pneumococcal vaccine impact on otitis media microbiology: A New Zealand cohort study before and after the introduction of PHiD-CV10 vaccine. Issue 33 (19th July 2016) - Best, Emma J.; Walls, Tony; Souter, Melanie; Neeff, Michel; Anderson, Trevor; Salkeld, Lesley; Ahmad, Zahoor; Mahadevan, Murali; Walker, Cameron; Murdoch, David; Mills, Nikki
Abstract: We compared the microbiology of middle ear fluid (MEF) in two cohorts of children having ventilation tube (VT) insertion; the first in the era of 7-valent Streptococcus pneumoniae conjugate vaccine (PCV7) and the second following introduction of the ten-valent pneumococcal vaccine (PHiD-CV10). Methods: During 2011 (Phase 1) and again in 2014 (Phase 2) MEF and NP samples from 325 children and 319 children were taken at the time of VT insertion. A matched comparison group had NP swabs collected with 137 children (Phase 1) and 154 (Phase 2). Culture was performed on all NP and MEF samples with further molecular identification of Haemophilus species, serotyping of S. pneumoniae, and polymerase chain reaction (PCR) testing on all MEF samples. Results: In Phase 2 immunisation coverage with ⩾3 doses of PHiD-CV10 was 93%. The rate and ratios of culture and molecular detection of the 3 main otopathogens was unchanged between Phase 1 and Phase 2 in both MEF and NP. Haemophilus influenzae was cultured in one quarter and detected by PCR in 53% of MEF samples in both time periods. S. pneumoniae and Moraxella catarrhalis were cultured in up to 13% and detected by PCR in 27% and 40% respectively of MEF samples . H. influenzae was the most common organism isolated from NP samples (61%) in the children undergoing VT surgery whilst M. catarrhalis (49%) was the most common in the non-otitis prone group. 19A was the most prominent S. pneumoniae serotype in both MEF and NP samples in Phase 2. Of Haemophilus isolates, 95% were confirmed to be non-typeable H. influenzae (NTHi) over both time periods . Conclusion: Following implementation of PHiD-CV10 in New Zealand, there has been no significant change in the 3 major otopathogens in NP or MEF in children with established ear disease. For these children non-typeable H. influenzae remains the dominant otopathogen detected.